Influence of Electric Current and Hard Anodizing Process Time of Aluminium toward Hardness and Layer Thickness - I Gst. Ngr. Nitya Santhiarsa (Jurnal Energi Dan Manufaktur, 2009)
Influence of Electric Current and Hard Anodizing Process Time of Aluminium toward Hardness and Layer Thickness